EFFECT OF PHOTOPERIODIC CONDITIONS ON THE LARVAE AND COCOON OF TASAR SILKWORM (Antheraea proyeli J.) - Dr. Meenakshi sharma1*, Anmol2, Ankita2, Bandana2, Kajal thakur2, Saveta chambial2, Dr. Amit sharma3* (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Environmental factors play critical role in the development and survival of insects and sericulture is the industry which totally rely on the silkworm. Photoperiodic induction acts as a sensitive index in Lepidopterans as well as in other insect groups. The present investigation was designed to study the impact of different environmental conditions viz. temperature, relative humidity and photoperiod on the laboratory cultured species of Antheraea proylei J.fed on Quercus serrata leaves. In an experimentation, equal (100 worms in each condition) number of larvae were divided into 3 groups: 1st group where larvae/cocoon were placed under 24 hour of light period, 2nd was under 24 hour dark and the 3rd was under normal conditions of 13 hrs Light:11 hrs Dark period with maintained temperature between 230C to 260C and humidity between 75-80%. It was observed that the body length, weight and life span varied in different photoperiodic conditions. The results showed that the preferable temperature range of 23-26 0C and relative humidity of 75 to 80% was desired for the growth and survival of the larvae and cocoon with 24 hour light and 24 hour dark period of light. Similarly relative humidity of 75 to 80% was the desired range for rearing and survival performances which influences its productivity and quality. 24 hour dark condition has highest survival rate of 75% followed by normal condition 72% and the light condition of 24%. The light condition worm had shown lowest survival rate as they are found to be infected with a disease named Nucleopolyhedrosis virus and Baculovirus. The present investigation revealed that at optimum conditions of temperature, humidity and photoperiodism showed better performances as compared to light conditions. Keywords: Antheraea proylei J., Lepidoptera, Photoperiod, Sericulture, Silkworm.